Internet and higher education: Prospects, challenges, problems - Yulia V. Smirnova, Larisa G. Orchakova, (Opción, 2020)
The purpose of this article is to develop a model for optimizing the modern concept of higher education information based on the key vulnerabilities determining its current state, problems and development prospects. The research method consists of analyzing, inductive and deductive reasoning; a systematic approach, comparative analysis, generalization of pedagogical experience related to knowledge assessment and also the educational process organization. Results demonstrate that the analysis of the current state, problems and prospects of the application of the Internet technologies in higher education was conducted within the research framework.